2002
DOI: 10.1002/hlca.200290015
|View full text |Cite
|
Sign up to set email alerts
|

Steric and Electronic Effects on an Antibody‐Catalyzed Diels–Alder Reaction

Abstract: Dedicated to Dieter Seebach on the occasion of his 65th birthday A series of substituted thiophene dioxides was tested as diene substrates for the antibody 1E9, which was elicited with a hexachloronorbornene derivative and normally catalyzes the inverse electron-demand Diels ± Alder reaction between 2,3,4,5-tetrachlorothiophene dioxide (TCTD) and N-ethylmaleimide (NEM). Previous structural and computational studies had suggested that the catalytic efficiency of this system derives in part from a very snug fit … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…The antibody‐catalysed Diels–Alder cycloaddition reaction between tetrachlorothiophene dioxide ( 5 ) and N ‐ethylmaleimide ( 6 ) proceeds via a transition state that looks very much like hexachloronorbornene derivative 7 (Scheme ), which was used as a hapten to generate the catalytic antibodies. The unstable intermediate spontaneously eliminates sulfur dioxide to give a product that rapidly undergoes in situ oxidation to produce N ‐ethylphthalimide . Moreover, site‐specific mutagenesis was utilised to produce a Cu II binding protein motif by introducing coordinating amino acids at geometrically appropriate positions in a thermostable protein and subsequently leading to the construction of a metalloenzyme mimic for Diels–Alder cycloaddition .…”
Section: Enzyme Mimics and Their Applicationsmentioning
confidence: 99%
See 2 more Smart Citations
“…The antibody‐catalysed Diels–Alder cycloaddition reaction between tetrachlorothiophene dioxide ( 5 ) and N ‐ethylmaleimide ( 6 ) proceeds via a transition state that looks very much like hexachloronorbornene derivative 7 (Scheme ), which was used as a hapten to generate the catalytic antibodies. The unstable intermediate spontaneously eliminates sulfur dioxide to give a product that rapidly undergoes in situ oxidation to produce N ‐ethylphthalimide . Moreover, site‐specific mutagenesis was utilised to produce a Cu II binding protein motif by introducing coordinating amino acids at geometrically appropriate positions in a thermostable protein and subsequently leading to the construction of a metalloenzyme mimic for Diels–Alder cycloaddition .…”
Section: Enzyme Mimics and Their Applicationsmentioning
confidence: 99%
“…Eur.J.2016, 22,8404 -8430 www.chemeurj.org duce N-ethylphthalimide. [287] Moreover,s ite-specific mutagenesis was utilised to produce aC u II binding protein motif by introducing coordinating amino acids at geometrically appropriate positions in at hermostablep rotein and subsequently leading to the construction of am etalloenzyme mimic for Diels-Alder cycloaddition. [288] Experimental evidence clearly showed that the Cu II is coordinatively bound to the amino acids at the artificial binding site where asymmetric Diels-Alder reactions occur.B yg rafting an ew active site (a Cu II -binding bidentate ligand)t oadimeric protein, Bose tal.…”
Section: "Diels-alderase" Forc Hemical Synthesismentioning
confidence: 99%
See 1 more Smart Citation
“…Initial velocities were determined by starch±I 2 bleaching at 606 nm at several concentrations of NEM while holding the concentration of TCTD constant at 150 mm. [26,38] The data were corrected for the uncatalyzed reaction and fitted to the Michaelis±Menten Equation:…”
Section: Kinetic Assaysmentioning
confidence: 99%